Design a MIMO printed dipole antenna for 5G sub-band applications - Haider Saad Najim; Mahmood Farhan Mosleh; Raed A. Abd-Alhameed (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
In this paper, a planar multiple input, multiple output (MIMO) dipole antenna for a future sub-6 GHz 5G application is proposed. The planar MIMO structure consists of 4 antenna elements with an overall size of 150×82×1 mm3. The single antenna element is characterized by a size of 32.5×33.7×1 mm3 printed on an FR-4 dielectric substrate with εr=4.4 and tanδ=0.02. The suggested antenna structure exhibits good impedance bandwidth equal to 3.24 GHz starting from 3.3 to 6.6 GHz with an S11 value of less than -10 dB (S11≤-10 dB) with antenna gain varying from 5.2 up to 7.05 dB in the entire band, which covers all the sub-6 GHz frequency band of the 5G application. Good isolation is achieved between the MIMO elements due to low surface waves inside the MIMO antenna substrate. The radiation of the MIMO antenna structure can be manipulated and many beam-types can be achieved as desired. The high-frequency structure simulator (HFSS) software package is used to design and simulate the proposed structure, while the CST MWS is used to validate the results.